Relationship between service quality, academic quality and satisfaction among students of Southern Thailand government universities: The moderating effect of value - Yamaqupta, Narueban (2014)
In the context of higher education institutions, particularly those located in southern Thailand, achieving student satisfaction is imperative for a number of reasons. Firstly, higher education institutions in this region are currently faced with situations that result in decreasing numbers of students. Secondly, competition tends to increase every year from both within and outside the country. Hence, low student satisfaction becomes an essential issue for higher education institutions to resolve. Moreover, indepth investigation on student satisfaction in this region is under-researched. Past studies have shown that student satisfaction is influenced by a variety of factors, including aspects related to quality and value. Therefore, this study sought to assess the relationship between service quality and academic quality on student satisfaction, and also to gauge the moderating effect of value using a multi-items measurement. Important instruments, such as the SERVPERF and the PERVAL scales, were used in this study. The respondents for this study were students enrolled in ten (10) government universities in the southern region of Thailand. A total of 768 questionnaires were distributed, and only 346 of them were usable. Approximately, 14 hypotheses were developed and tested with multiple regression and hierarchical regression analyses. The results indicated that several dimensions of service quality and academic quality were significantly related to student satisfaction, and the explanation power of the model increased from 25.6% to 33.5% when value moderated the relationship which explained the moderating effect of value. Plausible reasons for the findings were discussed within the context of the study. Both practical and theoretical contributions as well as recommendations for future research were made.